An Improved Novel Energy Efficient Method for Resource Allocation in Clouds Based on Ant Theory (International Journal of Engineering and Computer Science, 2018)
Cloud computing is the development of distributed computing, parallel computing and grid computing, or defined as the commercial implementation of these computer science concepts. The allocation of cloud computing resource is a hot topic. Many scholars have done some research in this area. This implementation have the intention of achieving the establishment of performance qualitative analysis on VM migration and process according to their deadline, then implemented in Cloudsim with Java language. A previous study also indicates change of instruction size (MIPS) will affect the response time and increase in instruction size (MIPS) versus VM decreases the response time. When metaphor size of VM is implemented against the VM bandwidth then no significant effect is found on response time and it remains constant for which these parameters are carried out for research. But in case of Cloudlet long length versus PM bandwidth a pattern is observed in which response time increases in proportionate manner. Using the modified approach the reduction in the down time and increase in efficiency of the various processes are resolved as shown in conclusion.